Reforming Sodom : Protestants and the Rise of Gay Rights - White, Heather Rachelle, 1974- (Book collections on Project MUSE., 2015)
With a focus on mainline Protestants and gay rights activists in the twentieth century, this book challenges the usual picture of perennial adversaries with a new narrative about America's religious and sexual past. The book argues that today's antigay Christian traditions originated in the 1920s when a group of liberal Protestants began to incorporate psychiatry and psychotherapy into Christian teaching.